2011
DOI: 10.1007/s00180-011-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

On the choice of a noninformative prior for Bayesian inference of discretized normal observations

Abstract: We consider the task of Bayesian inference of the mean of normal observations when the available data have been discretized and when no prior knowledge about the mean and the variance exists. An application is presented which illustrates that the discretization of the data should not be ignored when their variability is of the order of the discretization step. We show that the standard (noninformative) prior for location-scale family distributions is no longer appropriate. We work out the reference prior of Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Therefore, requisite (i) holds for the pdf (15), at least for this example. In [7] the approach described in section 3 was applied to the analysis of the data in table 1. Using the posterior obtained with prior (6) the results were x = 7.484 with u(x) = 0.021 for case 1 and x = 7.467 with u(x) = 0.016 for case 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, requisite (i) holds for the pdf (15), at least for this example. In [7] the approach described in section 3 was applied to the analysis of the data in table 1. Using the posterior obtained with prior (6) the results were x = 7.484 with u(x) = 0.021 for case 1 and x = 7.467 with u(x) = 0.016 for case 2.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the resolution problem has been addressed anew. Previous efforts have shown that in this inverse problem there seems to be some inherent difficulty that precludes obtaining a reasonably behaved posterior for the value of a quantity based solely on discretized measurement data [7]. These data refer indirectly to the quantity, because they have been filtered in a way that implies a loss of information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations